2009
DOI: 10.1074/jbc.m807536200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-mediated Phosphorylation and Activation of PDE3A Regulate cAMP Levels in Human Platelets

Abstract: The elevation of [cAMP] i is an important mechanism of platelet inhibition and is regulated by the opposing activity of adenylyl cyclase and phosphodiesterase (PDE). In this study, we demonstrate that a variety of platelet agonists, including thrombin, significantly enhance the activity of PDE3A in a phosphorylation-dependent manner. Upon vascular injury, platelets adhere to the newly exposed subintimal collagen and undergo activation leading to platelet spreading to cover the damaged region and release of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 32 publications
(36 reference statements)
3
75
0
Order By: Relevance
“…For example, ADP and epinephrine induce G i -protein-dependent inhibition of adenylyl cyclases. Thrombin stimulation of platelets has been reported to decrease cAMP by PKB-and PKC-dependent phosphorylation and activation of PDE3A (25)(26). Our experiments also confirmed that thrombin decreases cAMP levels in platelets (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, ADP and epinephrine induce G i -protein-dependent inhibition of adenylyl cyclases. Thrombin stimulation of platelets has been reported to decrease cAMP by PKB-and PKC-dependent phosphorylation and activation of PDE3A (25)(26). Our experiments also confirmed that thrombin decreases cAMP levels in platelets (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Increase of cGMP in thrombin-and collagen-stimulated platelets has been described in several publications (reviewed in Ref. 24), whereas cAMP has been shown to decrease in thrombin-stimulated platelets (25)(26). In our experiments, we could not detect any increase of cGMP in thrombin-or collagen-stimulated platelets (Fig.…”
Section: Ser157supporting
(Expert classified)
“…These data indicate that activating pathways rapidly phosphorylate and stimulate PDE3A to reduce cAMP levels below an inhibitory threshold whereas inhibitory PKA pathways may use PDE3A in a negative feedback loop. 14‐3‐3 binding to PDE3A might help to discriminate between activating and inhibitory pathways 71. Modelling of cyclic nucleotide levels confirms that PDEs are highly regulated exhibiting very low basal catalytic activity 72.…”
Section: Interactions At the Level Of Second Messengersmentioning
confidence: 99%
“…Thus, costimulation of Gq and Gi during platelet activation leads to PDE3A activation and AC inhibition resulting in a pronounced decrease in intracellular cAMP levels. Stimulation of PDE3A by thrombin is mediated by protein kinase C (PKC) which phosphorylates serines 312, 428, 438, 465, and 492 of PDE3A 71. A similar phosphorylation pattern is induced by treatment of platelets with collagen‐related peptide or by U46619.…”
Section: Interactions At the Level Of Second Messengersmentioning
confidence: 99%
“…However, later reports described that PDE inhibition induced by YTX, measured by electrochemical and colorimetric methods, 15 had no effect on cAMP levels in cardiomyocytes, 16 pointing to different effects depending on cell type and bringing up doubts about the specific role of YTX in PDE signaling. In platelets, it has been shown that PKC was engaged in the activation of PDE3 as happens with other human cellular models, 17,18 showing a link between these two enzymes. PDE modulators have been studied for their possible therapeutic effect in neurodegener-ative diseases.…”
Section: −3mentioning
confidence: 99%